Saudi Arabia : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Over the last few decades, the economy of Saudi Arabia has strengthened, as oil prices increased with the rebound in global economic activity. Despite this, vulnerabilities to a sustained decline in the oil price have increased. Executive Directors have commended the authorities for their continued stabilizing role in the oil markets. They have encouraged in creating more job opportunities for nationals and improving access to housing finance. They have encouraged the central bank to continue in strengthening the regulatory and supervisory framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet